Teaching digital competence: a systematic review - Romero-Hermoza, Rosa (2021)
Digital competences in teachers imply the development of functional capacities for the progress of virtual educational activities, and due to the current context (global health crisis), they need them as a priority of technology to insert themselves into digital citizenship. In the educational task, precisely in the work performance of the teaching staff, they serve as tools that provide sustainability for the development of virtual education. The objective of this research is to review the theories and foundations of digital skills in teachers located between the years 2017 and 2021. The applied methodology is the systematic review with processes of review, selection and analysis of 441 articles. 40 scientific documents were compiled under criteria of selection of the literature. The results conclude that digital competences are the skills that empower the individual to use digital media in different environments according to their qualities, the connectivist approach is related to digital competences, since the teacher creates an interaction system formed by nodes allowing him to organize a learning network, for this the educator must know, use, and relate the virtual media and environments.